Tourism development in Jerusalem - Moreno-Melgarejo, Alberto (2019)
Jerusalem has been attracting believers of the three great monotheistic religions for centuries. It has been erected over the time as the most sacred city for a large percentage of the world's population. It is currently attracting hundreds of thousands of international tourists whose main motivation is religious tourism and the visit of sacred places. However, it is a destination very exposed to the political controversy generated by the Palestinian-Israeli conflict for more than 70 years, and it continues to affect the image and competitiveness of the destination within the international panorama. In this article we analyze the causes explaining why Jerusalem is considered the capital of religious tourism worldwide, as well as the possibilities that tourism offers as a strategic argument to impose a certain historical narrative and an adequate climate of coexistence between Palestinian and Israelis communities.